THE SYMBOLIC DEVICES OF REALIZATION OF AUTHOR’S AESTHETIC CONSCIOUSNESS IN THE DRAMATIC POEM «THE SPHINX OF EUROPE» BY VASYL PACHOVSKY - Verlata, A. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the special features of the main idea of this drama and specification of symbolic images creation. It is emphasized on the main symbolic images, which are the personification of Ukrainian independence idea and fighting for unification of the native land. This idea was common for dramatic works by Vasyl Pachovsky. It is shown the basic conflicts, which help to grasp its substance and topicality for modern Ukrainian society.